PENGEMBANGAN BAHAN AJAR TEMATIK UNTUK SISWA KELAS IV - Westri Setyo Lestari; Herawati Susilo; Punaji Setyosari (Graduate School of Universitas Negeri Malang, 2017)
The purpose of research is to develop the feasibility of thematic teaching materials of fourth grade students of elementary school. This research used Dick, Carey, and Carey development model. The materials are validated by content experts and technology learning experts. The trial stages of the teaching materials consist of one-to-one-tryout, small group tryout and field tryout. The result of the expert validation of the student's book is 88,6%, the result of the teacher's book is 86.8%. One-to-one-trying out result, student's book gets mean of 88%, teacher book gets 85%. The result of small group trial, student's book obtained average of 90,5%, teacher’s book equal to 91,6%. The results of field trials of student’s books obtained an average of 91% and teacher’s book of 96.6%. Based on these data, the student’s book and teacher’s book is very feasible to be used as a learning supplement.Penelitian ini bertujuan untuk mengembangkan bahan ajar tematik yang layak digunakan untuk siswa kelas IV sekolah dasar. Bahan ajar yang dikembangkan berbentuk buku siswa dan buku guru. Penelitian ini menggunakan model penelitian dan pengembangan Dick, Carey, dan Carey (2009). Bahan ajar tematik yang dikembangkan divalidasi oleh ahli isi/materi dan ahli teknologi pembelajaran. Tahapan uji coba bahan ajar terdiri atas uji coba perorangan, uji coba kelompok, kecil, dan uji coba lapangan. Hasil validasi ahli terhadap buku siswa sebesar 88,6%, hasil validasi ahli terhadap buku guru sebesar 86,8%. Hasil uji coba perorangan, buku siswa memperoleh rerata sebesar 88%, buku guru memperoleh 85%. Hasil uji coba kelompok kecil, buku siswa memperoleh rerata sebesar 90,5%, buku guru sebesar 91,6%. Hasil uji coba lapangan buku siswa memperoleh rerata sebesar 91% dan buku guru sebesar 96,6%. Berdasarkan data-data tersebut, maka buku siswa dan buku guru sangat layak digunakan sebagai suplemen pembelajaran.